2005
DOI: 10.1002/adsc.200404239
|View full text |Cite
|
Sign up to set email alerts
|

Base-Catalyzed Condensation of 2-Hydroxybenzaldehydes with α,β-Unsaturated Aldehydes - Scope and Limitations

Abstract: The base-catalyzed condensation of a,b-unsaturated carbonyl compounds with 2-hydroxybenzaldehydes yielding tetrahydroxanthones and dihydrobenzopyrans has been investigated. A novel access to highly functionalized dihydrobenzopyrans via a mild generation of the dienol of senecialdehyde and subsequent conjugated aldol reaction has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Reaction path a: synthesis of 2,2-dimethyl-2H-chromene-3-carbaldehydes 3 and 9-methyl-8,12-dioxatricyclo [7.3.1.0 2,7 ]trideca-2,4,6-trien-11-ols 4. [15] Reaction path b: preliminary synthesis of coumarin 6d-H.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction path a: synthesis of 2,2-dimethyl-2H-chromene-3-carbaldehydes 3 and 9-methyl-8,12-dioxatricyclo [7.3.1.0 2,7 ]trideca-2,4,6-trien-11-ols 4. [15] Reaction path b: preliminary synthesis of coumarin 6d-H.…”
mentioning
confidence: 99%
“…[15] The reactions, depicted in pathway a, Scheme 1, were performed in mixtures of dioxane and water. Upon screening for new conditions for the base-catalyzed condensation of salicylaldehydes with α,β-unsaturated aldehydes, we observed that a new product -a coumarinwas formed if the reactions were carried out in ionic liquids with 2-hydroxy-6-methoxy-4-methylbenzaldehyde (1d) and acrolein (5a) (pathway b, Scheme 1).…”
mentioning
confidence: 99%
“…Similar observations have been reported for the analogous condensation of salicylic aldehydes with prenal. [24] The ratio of the oxa-Michael product to the competitively formed aldol reaction product was shifted in favor of the latter with increasing basicity of the base. Additionally, the usage of a weaker base should also enhance the stability of 4-hydroxycyclohexenones such as 10g and 13b during the condensation reaction.…”
Section: Entrymentioning
confidence: 98%
“…For example, the N-methylation of indoles, the condensations of unsaturated aldehydes or ketones and the simple additions of alkyne [27,28,[42][43][44][45][46][47][48][49] To sum up, DABCO, as a small organic molecular catalyst has an important place in organic synthesis. Compared with the traditional transition-metal catalysts, DABCO is a widely used reagent which is stable, contamination-free, convenient and cheap.…”
Section: Application Of Dabco In Other Organic Synthesis Reactionsmentioning
confidence: 99%